2020
DOI: 10.1002/ctm2.192
|View full text |Cite
|
Sign up to set email alerts
|

NK cells in human visceral adipose tissue contribute to obesity‐associated insulin resistance through low‐grade inflammation

Abstract: Dear Editor, Obesity leads to macrophage infiltration in adipose tissue (AT), causing chronic low-grade inflammation (LGI). This in turn leads to insulin resistance, contributing to F I G U R E 1 NK cells from obese subjects promote inflammatory macrophage polarization and produce increased levels of TNF. A, Bloodderived NK cells from control (n = 6; BMI 24.0 [22.5-26.2] kg/m 2 ; white bars) and obese individuals (n = 8; BMI 41.5 [40.4-47.0] kg/m 2 ; black bars) were isolated and co-cultured with either human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“… 177 In men with abdominal obesity, the accumulation of NK cells in vWAT was associated with vWAT volume, low-grade inflammation, inflammatory macrophage polarization and insulin resistance. 178 The proportion of ST2 + Tregs in vWAT was severely reduced in obese mice fed a high fat/sucrose diet. 170 IL-33 treatment fully restored the level of ST2 + Tregs in vWAT and reduced vWAT inflammation, hyperinsulinemia and insulin resistance.…”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 98%
“… 177 In men with abdominal obesity, the accumulation of NK cells in vWAT was associated with vWAT volume, low-grade inflammation, inflammatory macrophage polarization and insulin resistance. 178 The proportion of ST2 + Tregs in vWAT was severely reduced in obese mice fed a high fat/sucrose diet. 170 IL-33 treatment fully restored the level of ST2 + Tregs in vWAT and reduced vWAT inflammation, hyperinsulinemia and insulin resistance.…”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 98%
“…A relationship between NK cells and insulin resistance have been reported by several (11,29). However, such associations could not be found in our cohort when examining the individual proteins and by using HOMA-IR as a measure of insulin resistance.…”
Section: Discussionmentioning
confidence: 79%
“…Studies have shown that the increase in free fatty acid (FFA) and abnormal adipokines caused by obesity can lead to insulin resistance and may lead to the onset of MetS ( 41 , 42 ). Obesity, especially visceral obesity, leads to chronic low-grade inflammation of the whole body, which is attributed to the production of inflammatory cytokines by fat cells and infiltrating immune cells, forming a carcinogenic environment ( 43 , 44 ). Previous studies reported inconsistent results on BMI and bladder cancer risk, some studies have shown a positive association ( 45 , 46 ), and several studies reported no significant correlation ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%